Mesh mash: Legal fishing nets cause most bycatch mortality of endangered South Asian river dolphins. (December 2020) - Kelkar, Nachiket; Dey, Subhasis
Abstract: Bycatch mortality from entanglement in fishing nets is a major threat to the conservation of endangered cetacean species, including South Asian river dolphins Platanista . Bycatch mortality of Platanist a (estimated at around 5% of total population size per year) is often blamed on the use of illegal fishing gears (especially gillnets), and poor law enforcement. In our perspective paper, we found that over two-thirds of reported bycatch mortality of Platanista occurred in legal nets, from sources available on mesh sizes implicated in river dolphin bycatch. This finding highlights the need to critically revisit net mesh size regulations in existing fishery laws to effectively tackle the threat of bycatch. We show that minimum mesh size regulations have a colonial legacy and are a common element of fishery laws across three major range countries of Platanista : India, Pakistan, and Bangladesh. We also show that the existing gaps between fishery laws and wildlife conservation laws are unlikely to be helpful in prevention of bycatch. Especially in the event of accidental bycatch mortality in legal nets, enforcement of wildlife laws protecting Platanista can get complicated. We discuss the consequences of Platanista bycatch in legal and illegal fishing nets for enforcement and fishers' compliance, and explore associated factors in small-scale capture fisheries that can constrain bycatch mitigation efforts. Highlights: Most bycatch mortality of South Asian river dolphins occurs in legal fishing nets. Identifies gaps in existing fishery laws across river systems of the Indian subcontinent. These gaps may hinder effective mitigation of bycatch mortality of endangered river dolphins.